Menjadi Pembawa Damai - Harefa, Surya (Verbum Christi: Jurnal Teologi Reformed Injili, 2025)
The biblical idea of peace is deeply shaped by the meaning of the Hebrew word shalom. This term signifies more than just a ceasefire or the end of war and conflict. Shalom refers to a state of overall well-being and harmonious relationships with God, other people, and creation. The Fall into sin has taken shalom away from humanity. Nevertheless, Christ's redemptive work restores shalom to human life.